The gospel embodied in African traditional religion and culture with specific reference to the cult of ancestor veneration and the concept of salvation : an inculturation hermeneutic - Human, Dirk J. (University of Pretoria, 2013)
Thesis (DPhil (Biblical and Religious Studies))--University of Pretoria, 2006.